Evaluation of grid performance under time-series DERs and storage penetration scenarios - Aydın, Hatice; Özcan, Muciz (İdris Karagöz, 2026)
Elektrik şebekesi karbon nötr geçişte çok önemlidir. Bu geçişte, yenilenebilir kaynaklardan elde edilen üretim hızla artmaktadır. PV ve rüzgâr gibi hava ve zamana bağlı sistemlerde üretim ve tüketim talebini dengelemek için enerji depolamaya ihtiyaç duyulmaktadır. Bu makale, dağıtık enerji kaynaklarının (DEK) bağlanmasıyla bir trafo merkezinden beslenen şebekenin modellenmesi, simülasyonu ve performans çalışmasını ve üretim ile tüketim arasındaki kararlı durum ve 24 saatlik zamanla değişen koşullar için şebeke üzerindeki etkisinin değerlendirilmesini sunmaktadır. Tüm modeller hem zamanla değişen simülasyonlar hem de kararlı durum yük akışı analizi için olasılıksal olarak türetilmiştir. Simülasyon sonuçlarına göre, DEK' lerin doğru penetrasyonda gerilim kararlılığına olumlu katkıda bulunduğu, kısa devre katkısının %1,5-2 arasında olduğu, ancak penetrasyonun yoğun olduğu durumlarda %3,5 katkı gözlendiği, gerilim profilinin 1,04 pu' ya ulaştığı görülmektedir. Doğru penetrasyonun olduğu durumlarda, üretilen enerjinin %70'i yerinde tüketilerek hat kayıpları azaltılır. Reaktif güce katkısı %5 ile %7,5 arasındadır. Zamanla değişen analizler, BEDS' in dahil edilmesiyle günün belirli saatlerinde enerji talebinin %93'ünün DEK' lerden karşılanabileceğini ve yüke enerji sağlamak için tatmin edici bir şekilde çalıştığını göstermektedir.

The electricity grid plays a pivotal role in facilitating the transition to a carbon-neutral economy. Concurrently, there has been a marked increase in the generation of renewable energy. Energy storage is imperative to ensure the balance between generation and consumption demand in weather- and time-dependent systems, such as photovoltaic and wind energy. This article presents the modeling, simulation, and performance study of a grid fed from a substation connected to DERs, and an assessment of its impact on the grid for steady state and 24-hour time-series conditions between generation and consumption. All models are derived probabilistically for time-series simulations and steady-state load flow analysis. According to the simulation results, DERs have a beneficial effect on voltage stability, provided the penetration level is appropriate. At the optimal penetration level, the short-circuit contribution of DERs is estimated to be between 1.5% and 2%. However, when the penetration level is increased, the contribution increases to 3.5%, resulting in a voltage profile of 1.04 pu. In instances of optimal penetration, 70% of the generated energy is consumed on site, thereby reducing line losses. The contribution to reactive power ranges from 5% to 7.5%. In the time-series analysis, with the inclusion of BESS, it has been demonstrated that 93% of the energy demand can be met by DERs at certain times of the day, and that it functions satisfactorily to provide energy to the load.
Evaluation of grid performance under time-series DERs and storage penetration scenarios
Keywords: Electrical Circuits and Systems; Elektrik Devreleri ve Sistemleri [EN] Electrical Energy Storage; Elektrik Enerjisi Depolama [EN] Electrical Energy Transmission; Networks and Systems; Elektrik Enerjisi Taşıma; Şebeke ve Sistemleri [EN] Photovoltaic Power Systems; Fotovoltaik Güç Sistemleri